Hawks and Doves: Financial market perception of Western support for Ukraine - Matthias Neuenkirch; Maria Repko; Enzo Weber (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2023)
Since the Russian invasion of Ukraine on February 24, 2022, the West has been intensively discussing its support strategy. Hawkish positions of strengthening Ukraine via armaments, financial resources, and sanctions against Russia compete with dovish views of avoiding further escalation of the military and geopolitical conflict. News from the war became a dominating factor for international politics and the world economy. In this paper, we analyse how international financial markets perceived this news, especially on Western positions. We create a comprehensive data set of news related to the war and measure reactions of five key financial markets. The results show that stronger support for Ukraine had a positive impact after the first weeks of the war when the Ukrainian position in the war improved, but a negative or at least less positive influence before. Thus, financial markets seem to have perceived support as a risk of further escalation threatening global economic activity in the first phase. However, a hawkish line was a positive signal for financial markets after the change in perceptions. The results also confirm that the war and escalation in general had harmful effects on international financial markets.
Keywords: G14; H56; 330; Conflict; Event Study; Financial Markets; News; Russia; Sanctions; Ukraine